Analysis Determinants of Carbon Emissions Disclosure in the Energy Sector - Lestari, Rahmah; Khofifah, Sayyimatun; Nur Hadiyati, Siti (Journal of Accounting and Finance Management, 2025)
Carbon emissions disclosure aims to analyze how companies report carbon emissions transparently. Addressing carbon emissions is an urgent priority that requires swift and decisive action. The energy sector is a major contributor to carbon emissions, and emissions disclosure is voluntary. The novelty of this research is testing the institutional ownership variable. Purposive sampling, secondary data, and quantitative techniques were used in the sample selection process for this research.  Descriptive statistics, the normality test, and the multicollinearity test are the methods of analysis employed.  The research's goal is to show that, whereas institutional ownership and environmental performance have little bearing on disclosure, leverage and competitiveness levels do. According to the research's findings, firms are encouraged to disclose carbon emissions more publicly due to financial pressures and industry competitiveness, both as a way to be more environmentally responsible and as a tactic to improve their reputation. These findings imply that companies typically disclose carbon emissions in response to external pressures, such as competition and the need to maintain financial stability, rather than because of a commitment to environmental sustainability.